PENGARUH PENDAPATAN ASLI DAERAH, DANA ALOKASI UMUM, DAN DAK TERHADAP BELANJA LANGSUNG - Solichah, Dewi; Andayani, Andayani (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is aimed to find out whether the local own source revenue, general allocation fund, specifics allocation fund to the direct expenditure all districts / cities in East Java Province. The population is all districts/cities in East Java province. The sample collection technique has been done by using purposive sampling method and the samples are 35 districts/cities in East Java province. The secondary data has been obtained from the audit board of the Republic of Indonesia East Java province representative. The research analysis is the multiple linear regressions analysis which has been carried out by using SPSS program to examine local own source revenue, general allocation fund, specifics allocation fund give positive influence to the direct expenditure. The result of this research shows that local own source revenue, general allocation fund, specifics allocation fund give positive influence to the direct expenditure.Keywords: Local own sources revenue, general allocation fund, specifics allocation fund, direct expenditure